Managing quality in housing - Marosszeky, Marton; Forsythe, Perry; Lipscomb, Peter A. (University of New South Wales, Building Research Centre and Audio-Visual Unit for New South Wales Building Services Corp., 1987)
Examines the "night first time" philosophy as applied to the building industry by means of a quality management plan.